2009
DOI: 10.1248/bpb.32.1114
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity of Fragrance Ingredients against Legionella pneumophila

Abstract: In the current study we investigated the antibacterial activity of fragrance ingredients against Legionella pneumophila, a causative agent of severe pneumonia. Among the 41 different fragrance ingredients tested, we found that the natural fragrance ingredients oakmoss (OM) and birch tar oil (BT), which contain many components, exhibit potent antibacterial activity. The minimum inhibitory concentration (MIC, % (v/v)) of OM and BT were 0.0020 and 0.0024, respectively and were lower than that of cinnamic aldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…However, neither oakmoss itself nor the 20 individual compounds exhibited antibacterial activity against other Gram-negative and Gram-positive bacteria tested. 6) All Gram-negative bacteria possess an outer membrane that imparts a hydrophilic surface to the cell. Small hydrophilic compounds can traverse the outer membrane through porin proteins that form hydrophilic trans-membrane channels that exclude hydrophobic compounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, neither oakmoss itself nor the 20 individual compounds exhibited antibacterial activity against other Gram-negative and Gram-positive bacteria tested. 6) All Gram-negative bacteria possess an outer membrane that imparts a hydrophilic surface to the cell. Small hydrophilic compounds can traverse the outer membrane through porin proteins that form hydrophilic trans-membrane channels that exclude hydrophobic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were serially diluted with BYE-α as described previously. 6) Each diluted sample (50 µL) was mixed with 50 µL of bacterial suspension adjusted to 6.0×10 5 colony forming units (CFU)/mL with BYE-α and incubated at 37°C for 48 h. To determine the MICs against other bacterial strains, bacterial suspensions were adjusted to 1.0×10…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antibacterial characteristics of oakmoss and its components have been reported by us previously. 11,12) Specifically, we demonstrated that oakmoss and its components exhibited antibacterial activities against members of the genus Legionella, including clinical and environmental isolates of L. pneumophila and other Legionella spp. 12) In the present study, we investigated the effect of oakmoss and its components on L. pneumophila biofilm formation and the bactericidal activity of oakmoss against the bacterium in biofilms.…”
mentioning
confidence: 97%